Perfectionism and writing anxiety as predictors of Iranian EFL learners’ performance in IELTS writing module: a multi-dimensional perspective - Khosravi, Robab; Mohammadi, Elham; Esmaeili, Nazanin; Zandi, Hamed (Frontiers in Education, 2023)
This study aimed to investigate the relationship between Iranian EFL Learners’ perfectionism and writing anxiety and their performance in the IELTS Writing Module. To this end, 68 intermediate students majoring in English Translation at University of Zanjan were matched for the study through Oxford Quick Placement Test. Multidimensional Perfectionism Scale developed and validated by Hewitt & Flett (1991) and Second Language Writing Apprehension Test devised by Cheng (2004) were administered to the participants. The participants were then asked to write an on a topic assigned from IELTS Writing Task 2. The findings of the study indicated that two dimensions of perfectionism (i.e., other-oriented and socially prescribed) are positively associated with the learners’ writing performance, while a significant negative relationship was found between the learners’ writing anxiety and their writing performance. Multiple regression analyses suggested that self-oriented, socially prescribed, somatic, and behavioral variables were significant predictors of writing performance. The implications highlight deploying strategies to alleviate writing anxiety in L2 classrooms; promoting a safe and stress-free educational environment and boosting learners’ self-confidence are among the strategies to be considered by educational policy-makers, practitioners, and examiners.